The overview of Asean rice trade toward Asean Integrated Food Security (AIFS) / Evi Nurifah Julitasari - Julitasari, Evi Nurifah (Faculty of Business and Management, 2014)
ASEAN takes serious effort to address the challenge of Food Security, within the region of Southeast Asia. Especially for rice trade among ASEAN country was taken place a long ago. In 2015 we would be integragted market. The aims of study are (1) to analysys the potential of rice supply and demand (2) the effect of trade restriction (export and import restriction). The models were constructed by econometric simulation analysis with time series data from 1984-2007. The results shows: (1) the trend of ASEAN paddy production was increasing. The average increase of the ASEAN paddy production was 130,46 MT/year with the rate 2,84 percent/year (2) the effect of export restriction will be increase an export price more than 10 percent, and the effect of import restriction will be increase an import price in all importer countries.